APPLICATION OF 3D POINT CLOUD DATA FOR CUT SLOPE MONITORING (Geologica Macedonica, 2024)
This paper discusses the monitoring of slope instability during the construction of an expressway. As a basis, appropriate geological and engineering-geological investigations were carried out, supported by the appli-cation of practical sensing and analysis techniques, including drone-based imaging. The main goal is to present an example of the detection and monitoring of slope movements using a 3D point cloud obtained from the low-cost, remote, and precise SfM (Structure from Motion) technique, and appropriate software. The analyzed area represents a small part of a slope cut on the A2 Expressway Kriva Palanka-Stracin, in the Republic of Macedonia, which is under construction. The slope cut is excavated in albite-epidote-chlorite schists. In geological terms, it was found that this part of the cut has favorable conditions for the occurrence of instability. Four different point cloud sets were analyzed from four different surveys conducted over a total of five months, both before and after the occurrence of the instability. Multitemporal geomorphic changes in the unstable area were identified by comparing the SfM-derived point clouds in pairs. 3D distances were estimated with the multiscale model-to-model cloud comparison for each pair of point clouds. The results show that the displacements on the slope range up to 70 cm. Also, the five-month observation period shows that the instability is still active. Additional geometrical features that enable easier visualization of changes in the terrain were utilized. The obtained results show that these procedures for the detection and monitoring of displacements of unstable terrains can be used as a regular technique for such purposes. The advantages are many, including swiftness, high detail of prospecting, and the possibility of determining very small movements.
Keywords: slope instability; 3D point cloud; SfM technique; monitoring